The Importance of Microbiological Monitoring in the Modern System of Preventing Healthcare-Associated Infections - E. V. Shatalova; O. V. Parakhina; A. I. Krasnoukhov (Антибиотики и Химиотерапия, 2020)
The article studies the etiologic structure and the level of resistance of significant pathogens of nosocomial infections isolated from patients in the multi-purpose hospitals of Kursk in 2014-2016 in order to determine the significance of microbiological monitoring in the modern system of preventing healthcare-associated infections (HAIs). The structure of the clinical flora is dominated by bacterial and Candida-bacterial associations (51.9%), which is not consistent with the results of similar studies. The dominant associates are fungi of the Candida genus (15.8%), Pseudomonas aeruginosa (12.3%), the third place is occupied by coagulase-negative staphylococci (8.7%). There is a general tendency to increase antibiotic resistance to traditional drugs and significant variability to modern antibiotics, which under modern conditions clearly defines two trends - frequent changes in the species composition of associates and the emergence of the problem of drug resistance. Consequently, the only guideline for the selection of adequate therapy for nosocomial infections should be the data of microbiological monitoring as the main component of HAIs prevention system.